2009
DOI: 10.4314/aga.v20i2.1742
|View full text |Cite
|
Sign up to set email alerts
|

Germination et accumulation des métabolites chez les plantules de légumineuses cultivées sous stress salin

Abstract: RESUMELes effets de la salinité sur le comportement physiologique des graines, feuilles et tiges de cinq légumineuses ont été évalués afin d'identifier des critères précoces de sélection des espèces végétales tolérantes au sel. Quatre niveaux de salinité (0, 50, 100 et 200 mM de NaCl) ont été testés. Au bout de 4 semaines, trois séries de 7 plantes ont été prélevées dans chaque milieu de culture en vue d'évaluer les teneurs en lipides, protéines et proline. Ainsi, l'apport de NaCl a entraîné une baisse signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…It was low at (50-100 mM NaCl) in Pop1, Pop3, and 306 and did not differ significantly between populations at 150 and 200 mM. However, in two sensitive glycophytes, Phaseolus vulgaris and Glycine max, salt had a depressive effect that slowed the T50 from 50 mM NaCl with critical thresholds at 150 and 200 mM NaCl [29]. A study of tomato cultivars showed that the genotypes BARI Tomato-2, Mintoo, and Unnoyon were more tolerant to high salt stress in terms of T50 and root and shoot characteristics than other genotypes [32].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…It was low at (50-100 mM NaCl) in Pop1, Pop3, and 306 and did not differ significantly between populations at 150 and 200 mM. However, in two sensitive glycophytes, Phaseolus vulgaris and Glycine max, salt had a depressive effect that slowed the T50 from 50 mM NaCl with critical thresholds at 150 and 200 mM NaCl [29]. A study of tomato cultivars showed that the genotypes BARI Tomato-2, Mintoo, and Unnoyon were more tolerant to high salt stress in terms of T50 and root and shoot characteristics than other genotypes [32].…”
Section: Discussionmentioning
confidence: 88%
“…However, above 100 mM, this rate dropped to less than 67.5% for some varieties while for others, the germination rate exceeded 70%. The presence of NaCl also resulted in a significant decrease in germination in five legume species [29]. On the contrary, seeds exposed to a low concentration of 25 mM NaCl showed an increase in percent germination and germination index [30].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, various methods of resilience are used by plants to cope with salinity stress through mechanisms leading to osmotic adjustment. Taffouo et al (2009) reported that seed germination rate can be used as a first criterion for the screening of legumes populations and species tolerant to salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…En produisant des grains et des fourrages de qualité, la culture des légumineuses peut augmenter le revenu brut des exploitations en réduisant les charges en engrais notamment grâce à la fixation symbiotique de l'azote atmosphérique (Carsky et al, 2003). Parmi ces légumineuses, le niébé (Vigna unguiculata (L) walp), l'arachide (Arachis hypogaea) et le soja vert (Vigna radiata) sont les plus importants dans la plupart des communautés africaines où ils sont cultivés (Taffouo et al, 2008). Elles exercent une influence favorable sur la fertilité des sols grâce à la symbiose fixatrice d'azote avec les souches de rhizobium.…”
Section: Introductionunclassified